Total phenolic and flavonoids content, and antioxidant activity of kratom (Mitragyna speciosa Korth.) leaf ethanol extract - MASRIANI, MASRIANI; MELANIA, PURNAMA; MUHARINI, RINI; ALIMUDDIN, ANDI HAIRIL; SARTIKA, RODY PUTRA (Universitas Syiah Kuala, 2024)
This study aims to determine and compare antioxidant activity, total phenolics, flavonoids, and the relationship of phenolic and total flavonoids with the antioxidant activity of the three kratom variants. The ethanol extract of the third variant of kratom leaves was obtained by maceration. Through the antioxidant activity test using DPPH method, all three extracts showed strong antioxidant activity with IC50 values of 26.39, 30.25, and 30.59 g/mL. The relationship of total phenolics and flavonoids with antioxidant activity was determined by the Pearson correlation test. Examination of total phenolic content using the Folin-Ciocalteu method with successive results for green, red, and white kratom are 6.11, 8.67, and 9.09 mg GAE/g extract. Examination of total flavonoid content using the colorimetric method for green, red, and white kratom were 0.86, 0.68, and 1.13 mg QE/g extract, respectively. The total phenolic content and antioxidant activity showed a correlation coefficient value of -0.32 (P0.05), and the total flavonoid content to antioxidant activity showed a correlation coefficient value of 0.81 (P0.05). Thus, all three variants of kratom have potency as natural antioxidants, but their total phenolic and flavonoid content does not influence their antioxidant activity.